Effect of electronic angular momentum exchange on photoelectron anisotropy following the two-colour ionization of krypton atoms - Saquet, N.; Holland, D.M.P.; Pratt, S.T.; Cubaynes, D.; Tang, X.; Garcia, G.A.; Nahon, Laurent; Reid, Katharine L. (American Physical Society, 2016)
We present photoelectron energy and angular distributions for resonant two-photon ionization via several low-lying Rydberg states of atomic Kr. The experiments were performed by using synchrotron radiation to pump the Rydberg states and a continuous wave laser to probe them. Photoelectron images, recorded with both linear and circular polarized pump and probe light, were obtained in coincidence with mass-analyzed Kr ions. The photoelectron angular distributions and branching ratios for direct ionization into the Kr+ 2P3/2 and 2P1/2 spin-orbit continua show considerable dependence on the intermediate level, as well as on the polarizations of the pump and probe light. Photoelectron angular distributions were also recorded with several polarization combinations following two-colour excitation of the (2P1/2)5f[5/2]2 autoionizing resonance. These results are compared with the results of recent work on the corresponding autoionizing resonance in atomic Xe.